International Economics / A Policy Approach - Kreinin E. Mordechai (Harcourt Brace Jovanovich, Publishers, 1983)
Preface, Foreign Trade in the American Economy, International Financial Relations, Statement of International Transactions, Market-Determined Exchange Rates, The International Currency System, National Income Determination in an Open Economy, Balance-of-Payments Adjustment Policies Under Fixed Exchange Rates, Exchange-Rate Adjustment, The Monetary Approach to the Balance of Payments, Exchange Control and Currency Inconvertibility, Reforming the International Monetary System, International Trade Relations, Why Nations Trade, The Commodity Composition of Trade, Protection of Domestic Industries: The Tariff, Other Barriers to Trade, U.S. Commercial Policy, International and Regional Trade Organizations among Developed Countries, International Mobility of Productive Factors, Appendices, Bibliography, Index.